High plasma omentin predicts cardiovascular events independently from the presence and extent of angiographically determined atherosclerosis. (January 2016) - Saely, Christoph H.; Leiherer, Andreas; Muendlein, Axel; Vonbank, Alexander; Rein, Philipp; Geiger, Kathrin; Malin, Cornelia; Drexel, Heinz
Abstract: Background and aims: No prospective data on the power of the adipocytokine omentin to predict cardiovascular events are available. We aimed at investigating i) the association of plasma omentin with cardiometabolic risk markers, ii) its association with angiographically determined coronary atherosclerosis, and iii) its power to predict cardiovascular events. Methods: We measured plasma omentin in 295 patients undergoing coronary angiography for the evaluation of established or suspected stable coronary artery disease (CAD), of whom 161 had significant CAD with coronary artery stenoses ≥50% and 134 did not have significant CAD. Results: Over 3.5 years, 17.6% of our patients suffered cardiovascular events, corresponding to an annual event rate of 5.0%. At baseline, plasma omentin was not significantly associated with metabolic syndrome stigmata and did not differ significantly between patients with and subjects without significant CAD (17.2 ± 13.6 ng/ml vs. 17.5 ± 15.1 ng/ml; p = 0.783). Prospectively, however, cardiovascular event risk significantly increased over tertiles of omentin (12.1%, 13.8%, and 29.5%, for tertiles 1 through 3; ptrend = 0.003), and omentin as a continuous variable significantly predicted cardiovascular events after adjustment for age, gender, BMI, diabetes, hypertension, LDL cholesterol, HDL cholesterol, and smoking (standardized adjusted hazard ratio (HR) 1.41 [95% CI 1.16–1.72]; p < 0.001), as well as after additional adjustment for the presence and extent of significant CAD at baseline (HR 1.59 [95% CI 1.29–1.97, p < 0.001). Conclusion: From this first prospective evaluation of the cardiovascular risk associated with omentin we conclude that elevated plasma omentin significantly predicts cardiovascular events independently from the presence and extent of angiographically determined baseline CAD. Highlights: No prospective data on the power of the adipocytokine omentin to predict cardiovascular events are available. This prospective cohort study for the first time shows that elevated plasma omentin significantly predicts cardiovascular events. Omentins predictive power is independent from classical cardiovascular risk factors and CAD.